Progress on diagnosis and treatment of functional parkinsonism - HUANG Pei; WANG Gang (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Functional parkinsonism (FP) is a disorder caused by psychological factors rather than neurodegeneration. Functional parkinsonism has a great influence on patients' quality of life and daily function. However, due to overlapping with some of the symptoms of Parkinson's disease (PD), the diagnosis of functional parkinsonism is often delayed or omitted. Early identification and diagnosis of functional parkinsonism is challenging and crucial to the treatment and prognosis of patients. This review summarizes the importance of clinical positive signs and auxiliary examinations in the diagnosis and differential diagnosis of functional parkinsonism. The differences of clinical features between functional parkinsonism and PD were compared in detail. This review aims to improve clinicians' diagnosis, differential diagnosis and treatment capabilities of functional parkinsonism.